Data Integrity and Data Governance - Santhosh Kumar, B. (IntechOpen, 2023)
Data integrity is the overall accuracy, completeness, and consistency of data. Data integrity also refers to the safety of data regarding regulatory compliance, such as GDPR compliance, and security. It is maintained by a collection of processes, rules, and standards implemented during the design phase. Data governance is the process of managing the availability, usability, integrity, and security of the data in enterprise systems, based on internal data standards and policies that also control data usage. Effective data governance ensures that data is consistent and trustworthy and does not get misused. This book provides a comprehensive overview of data integrity and data governance and their myriad applications.